Fabrication of ultrathin and flexible graphene-based devices for in vivo neuroprosthetics. (22nd January 2018) - Kireev, Dmitry; Shokoohimehr, Pegah; Ernst, Mathis; Montes, Viviana Rincón; Srikantharajah, Kagithiri; Maybeck, Vanessa; Wolfrum, Bernhard; Offenhäusser, Andreas
ABSTRACT: Graphene based devices have already proven to be extremely sensitive and very useful in a wide spectrum of bioelectronics research. In the manuscript we describe a method to fabricate arrays of graphene-based probes, requiring minimal number of fabrication steps, while maintaining overall device functionality. These polyimide-based probes are approximately 6 µm thick, therefore ultraflexible, yet robust and stable. Devices, such as graphene field effect transistors (GFETs) and graphene multielectrode arrays (GMEAs) have been designed, fabricated and tested for their performance. The flexible GFETs exhibit sensitivity, i.e. transconductance up to 700 µS/V, which an order of magnitude larger compared to typical silicon transistors. Multiple probe per wafer design allows us to fabricate different kinds of devices on one 4-inch wafer, consequently increasing a possible range of applications from e.g. retinal to cortical neuroprosthetics.